Characterization in Bakhtiar Ali's novel “Jamshid Khani Mamm” - Hamafaraj, Dilan Salam; Ali, Aram Omer; Abdulla, kanyaw Bakr; Ali, Srwa Tahir; Hussein, Hemn Abdullah; Mohammed, Rizgar Hussein; Qadir, Osama Rafiq; Mohammed, Azhi Amir; Abdulla, Mawdud Jabar (Raden Intan State Islamic University of Lampung, Indonesia, 2024)
This research entitled (Characterization in Bakhtiar Ali's Novel Jamshid Khani Mamm) is a new perspective on the concept of characterization and how Bakhtiar Ali deals with this concept in his novel Jamshid Khani Mamm. This study discusses the characters and their types and their use in the novel, an attempt to answer what is meant by characterization. What are the types of characters? How does Bakhtiar Ali create the characters in his novels? Can we see all kinds of characters in this novel? This research is conducted according to the (descriptive-analytical) approach, consists of an introduction and two main sections and finally the results are presented in several points.